2004
DOI: 10.1590/s0074-02762004000800007
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of rubidium marking in Aedes albopictus (Diptera: Culicidae): preliminary evaluation on persistence of egg labeling, survival, and fecundity of marked female

Abstract: Rubidium chloride (RbCl)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In this report, we evaluated the persistence and efficiency of 0.025 M RbCl and 0.0015 M CrCl 3 to mark T. brasiliensis nymphs. Trace elements have been successfully used to mark at least eight orders and 30 families of insects, with RbCl being the most frequently used marker (Hagler & Jackson 2001, Maciel-de-Freitas et al 2004. However, our results showed that RbCl had a very variable positivity and a decreasing persistence with the stage of T. brasiliensis.…”
Section: Discussionmentioning
confidence: 69%
“…In this report, we evaluated the persistence and efficiency of 0.025 M RbCl and 0.0015 M CrCl 3 to mark T. brasiliensis nymphs. Trace elements have been successfully used to mark at least eight orders and 30 families of insects, with RbCl being the most frequently used marker (Hagler & Jackson 2001, Maciel-de-Freitas et al 2004. However, our results showed that RbCl had a very variable positivity and a decreasing persistence with the stage of T. brasiliensis.…”
Section: Discussionmentioning
confidence: 69%
“…The dispersal ability of Ae. albopictus has been studied using a mark–release–recapture approach by several authors, but these studies were focused mainly on females and data are lacking for males, which are most important when applying strategies in which only males are released (Niebylski & Craig, 1994; Takagi et al , 1995; Maciel‐de‐Freitas et al , 2004, 2006). The removal of Wolbachia , as shown in this study, has no adverse impact on male fitness.…”
Section: Discussionmentioning
confidence: 99%
“…The top was covered with mosquito netting. These adults were kept in the laboratory at 25 ± 5° C and 60 ± 8% RH (Maciel‐de‐Freitas et al , 2004) and provided with 10% sucrose solution daily. The RH inside the vials varied from 80% to 85%.…”
Section: Methodsmentioning
confidence: 99%